Does hysteroscopy affect prognosis in apparent early- stage endometrial cancer?. Issue 4 (1st July 2008) - Ben-Arie, A.; Tamir, S.; Dubnik, S.; Gemer, O.; Ben Shushan, A.; Dgani, R.; Peer, G.; Barnett-Griness, O.; Lavie, O.
Abstract : The objective of the study was to compare the outcome measures of patients with endometrial adenocarcinoma diagnosed by endometrial biopsy, uterine curettage, or hysteroscopy. Medical records of 392 women diagnosed with apparent early-stage endometrial adenocarcinoma were reviewed. Data concerning the mode of diagnosis, histologic type and grade, surgical stage, peritoneal washings and lymph nodes status, and patient's outcome were retrieved. During the study period, 99 (25.3%) cases were diagnosed by endometrial biopsy, 193 (49.2%) by uterine curettage, and 100 (25.5%) by hysteroscopy. There were 347 (88.5%) cases of endometrioid adenocarcinoma and 45 (11.5%) of poor histologic types, including serous papillary, clear cell, and small cell cancer. Three hundred and sixteen (80.6%) patients had stage I disease, 8 (2.0%) stage II, and 68 (17.4%) stage III. Peritoneal cytology was positive in only one case. Recurrent disease occurred in 6.9% patients, of which 50% had local recurrence and 50% had distant. Recurrent disease was found in 15.2% patients diagnosed by endometrial biopsy, in 4.7% where uterine curettage was used, and in 5% when hysteroscopy was applied. No statistically significant difference in the survival rate between the different diagnostic methods applied was found, although a higher recurrence rate was noted following endometrial biopsy. After a median follow-up time of 25 months for patients undergoing hysteroscopy, there was no difference in recurrence rates and/or overall survival compared to other diagnostic procedures implying that hysteroscopy can be safely used in the diagnosis of endometrial cancer.